2016
DOI: 10.1016/j.celrep.2016.06.045
|View full text |Cite|
|
Sign up to set email alerts
|

Post-translational Modifications of OLIG2 Regulate Glioma Invasion through the TGF-β Pathway

Abstract: Summary In glioblastoma, invasion and proliferation are presumed to be mutually exclusive events; however, the molecular mechanisms that mediate this switch at the cellular level remain elusive. Previously, we have shown that phospho-OLIG2, a Central Nervous System-specific transcription factor, is essential for tumor growth and proliferation. Here, we show that modulation of OLIG2 phosphorylation can trigger a switch between proliferation and invasion. Glioma cells with unphosphorylated OLIG2S10, S13, S14 are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 47 publications
4
59
0
Order By: Relevance
“…Additionally, expression of the hyaluronic acid receptor CD44 was also increased in PNJ cultured GB3 cells as well as PNJ10 and PNJ20 cultured GB7 cells. CD44 expression has been proposed as a GSC marker and is commonly associated with an invasive phenotype [35,39]. Taken together, these data suggest that PNJ scaffolds promote expression of proteins that are known to regulate key GSC phenotypes such as self-renewal and invasion.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Additionally, expression of the hyaluronic acid receptor CD44 was also increased in PNJ cultured GB3 cells as well as PNJ10 and PNJ20 cultured GB7 cells. CD44 expression has been proposed as a GSC marker and is commonly associated with an invasive phenotype [35,39]. Taken together, these data suggest that PNJ scaffolds promote expression of proteins that are known to regulate key GSC phenotypes such as self-renewal and invasion.…”
Section: Discussionmentioning
confidence: 75%
“…In vivo limiting dilution is one of the gold standard methods for GSC identification. However, given that the control (neurosphere) cultures were previously characterized as containing GSCs [35,36], the in vitro limiting dilution and subsequent ELDA analysis were employed to measure quantitative differences in stem cell frequency [8,37]. Using this method, the stem cell frequency of PNJ cultured GB3 and GB7 cells was measured to be significantly increased (p < 0.01) for all scaffold formulations compared to neurosphere cultured controls (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ZEB1 may not only be required to achieve robust expression of SOX2 but it may also stabilize the SOX2 gene regulatory program post-transcriptionally by suppressing microRNAs that negatively regulate the transcript levels of SOX2 activated genes. Furthermore, a previous study demonstrated that Olig2 directly suppressed the expression of p21 in GBM (Ligon et al, 2007), which in turn represses Sox2 expression by binding to a Sox2 enhancer (Marques-Torrejon et al, 2013), and silencing OLIG2 was also shown to directly repress ZEB1 expression (Singh et al, 2016). Thus, OLIG2 appears to be required for SOX2 and ZEB1 expression in GBM suggesting that all three transcription factors may operate in a cross-regulatory interdependent fashion.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that differences in other genomic alterations apart from PDGFRα amplifications also play a role in subtype specification (Ozawa et al, 2014). Further analysis of the micro-environmental cues and intracellular mediators of this proliferation-differentiation (EGFR-PDGFRα) switch will provide additional mechanistic insight into the process of subtype conversion and may present novel therapies for patients with malignant gliomas (Singh et al, 2016). We therein propose a model where OLIG2 resides at the intersection of two cross regulatory loops in normal and malignant neural progenitors, forming a compulsory link between cell cycle regulation and sub-type specification, dictated through spatiotemporal protein modifications which promote self-renewal or fate choice.…”
Section: Discussionmentioning
confidence: 99%